Manajemen Interpersonal Perspektif Sumberdaya Manusia, Motivasi dan Kinerja dalam Organisasi - Zuhri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
The study aims to analyze matters relating to performance enhancement within the organization, being reviewed from various aspects, such as; 1. Overview of MSDM, 2. Reviews on motivation, 3. Overview of the performance, 4. An overview of interpersonal skills. With focus discussion. 1what is the basic concept of human resource management in the organization, 2 how the basic concept of motivation in the organization, 3 how basic concept of performance in the organization, 4 how the concept of human resources, motivation, and performance in management Interpersonal. Types of correlational qualitative research. Data analysis techniques with the research path of 1 successful factor that determines individual performance and the team in the organization are knowledge or skill and willingness to walk together.